Internal Support System of Inclusive Education - Witri Shafira; J. Juhanaini; Zulkifli Shiddiq (JASSI ANAKKU, 2021)
The purpose of this study was to reveal how the internal part of the school supports the organizers of inclusive education at 093 Tunas Harapan Cijerah Elementary School. The method used in this research is descriptive with a qualitative approach, the subjects of this research are school principals and teachers at 093 Tunas Harapan Cijerah Elementary School. Based on the results of the study, the internal support system at 093 Tunas Harapan Cijerah Elementary School is still far from ideal, this is because each party as part of internal support has not fully supported the implementation of inclusive education at 093 Tunas Harapan Cijerah Elementary School. Furthermore, this has an impact on the learning and mobilization of students with special needs in schools. The learning of students with special needs in practice is completely left to the special supervisory teacher, therefore there is a need for a reassessment of how teachers as internal support the learning of students with special needs in the classroom.